(untitled) (Veterinary Science, 2023)
The objective of this study was to determine the forage quality of goat intake in a natural pasture in the Meseta Central del Sur de Mendoza (Argentina). The test was carried out by simulating the goat intake with manual harvesting of the plant species that make up the intake of Creole goats under direct grazing, including the species that were present above 1% in each of the phenological moments. Six samples were simulated for each vegetative period and the percentage of Crude Protein, Neutral Detergent Fiber, Acid Detergent Fiber, Digestibility of Dry Mater (DMS) and Metabolic Energy (ME) were evaluated for each sample. The difference between the means according to phenological moment was made by ANAVA and Tukey’s test, for the variables evaluated. The results obtained showed that at the time of regrowth is when the highest level of crude Protein (20.51±1.14%) and Expected Digestibility of Dry Matter (72.13±1.68%) shows the goat intake, with a significant statistical difference (p<0.05), in relation to the other phenological moments considered. Despite this, forage quality levels both in pre-flowering (13.92±0.83% and DEMS 67.66±2.27%) and in vegetative rest (P.B. 9.93±0.62% and DEMS 61.33±1.72%) can be considered good, since they are enough to cover the needs of the Creole goats used in this trial. It can be concluded by saying that the Criolla goat in direct grazing of the vegetation in the South Central Plateau of Mendoza maintains a good quality forage intake throughout the year based on the selection of the plant species it consumes.